Evaluasi Program Sekolah Inklusif di SMA Negeri 10 Kota Ternate - Marasabessy, Fachria Y (Social and Political Science Faculty - Universitas Tidar, 2023)
Access to education for all has become a basic right and is protected by the constitution. However, education for children with special needs has not yet fully received services that depict justice, equality and equality in accordance with the constitutional mandate. The aim of this research is to carry out a mapping of the implementation of inclusive education in high school improvement schools and carry out evaluations to strengthen the program in the future. The method used is descriptive qualitative. The informants chosen to obtain primary and secondary data came from the principal, subject teachers, and the person in charge of the inclusive school of SMA Negeri 10 Ternate City. Data collection using interviews, observation and study documentation was analyzed in several categories to answer the research objectives. The results found that SMA Negeri 10 had implemented the principles of inclusive education by providing access to children with special needs to receive the same educational services as regular students. The evaluation shows that it is necessary to strengthen the human resources aspect because there is still a lack of training for teachers. Then provide room facilities and reading materials for children with special needs.